1994
DOI: 10.1002/cne.903400408
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of NMDA receptors increases cell death and birth in the developing rat dentate gyrus

Abstract: Excitatory input regulates cell birth and survival in many systems. The granule cell population of the rat dentate gyrus is formed primarily during the postnatal period. Excitatory afferents enter the dentate gyrus and begin to form synapses with granule cells during the first postnatal week, the time of maximal cell birth and death. In order to determine whether excitatory input plays a role in the regulation of cell birth and survival in the developing granule cell layers and their germinal regions, the sube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
3
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 224 publications
(125 citation statements)
references
References 71 publications
4
117
3
1
Order By: Relevance
“…Only after several studies had confirmed the early reports by Altman and Das (1965) and Kaplan and Hinds (1977) that adult hippocampal neurogenesis indeed occurs, and after improved methods had been introduced to quantitatively identify new neurons with relative ease (Kuhn et al, 1996), did questions of function become imminent. The first studies, particularly the work by Bruce McEwen's group, focused on the negative regulators of adult hippocampal neurogenesis (Gould et al, 1992(Gould et al, , 1994, especially severe stress (Gould et al, 1997). In contrast, our own findings that living in an enriched environment led to a robust increase in adult hippocampal neurogenesis indicated that adult hippocampal neurogenesis might indeed be regulated in relation to normal behavior (Kempermann et al, 1997(Kempermann et al, , 1998a.…”
mentioning
confidence: 78%
“…Only after several studies had confirmed the early reports by Altman and Das (1965) and Kaplan and Hinds (1977) that adult hippocampal neurogenesis indeed occurs, and after improved methods had been introduced to quantitatively identify new neurons with relative ease (Kuhn et al, 1996), did questions of function become imminent. The first studies, particularly the work by Bruce McEwen's group, focused on the negative regulators of adult hippocampal neurogenesis (Gould et al, 1992(Gould et al, , 1994, especially severe stress (Gould et al, 1997). In contrast, our own findings that living in an enriched environment led to a robust increase in adult hippocampal neurogenesis indicated that adult hippocampal neurogenesis might indeed be regulated in relation to normal behavior (Kempermann et al, 1997(Kempermann et al, , 1998a.…”
mentioning
confidence: 78%
“…These data indicate that NMDAR, characterized by their high Ca 2+ permeability, are the link between glutamate, Ca 2+ and neuronal cell death. On the other hand, it was shown that blocking NMDAR with MK-801 decreases the density of healthy cells in the dentate gyrus (Gould et al, 1994), indicating that a moderate flow of Ca 2+ ions through NMDAR is beneficial for neurons, while Ca 2+ overload, linked with an excessive NMDAR activation, is deleterious (NMDAR paradox) (Hardingham and Bading, 2003).…”
Section: Role Of Glutamatementioning
confidence: 99%
“…Moreover, the application of histamine (100 M) to brain slices containing striatal neurons has resulted in a concentrationdependent, NMDA receptor-mediated neuronal swelling, ultimately leading to H 2 receptor-mediated neuronal death (Colwell and Levine, 1997). Although the exact intracellular mechanisms mediating the neurotoxic effect of high histamine concentrations are poorly known, the effects mediated through NMDA receptors could be of importance, because the normal NMDA receptor function is of crucial importance for neuronal survival in the immature hippocampus (Gould et al, 1994;Katz and Shatz, 1996;Ben-Ari, 2001;Manent et al, 2005), and any disturbances may enhance neuronal damage.…”
Section: Mechanisms Of Histamine-mediated Neuroprotective Effectmentioning
confidence: 99%